2018
DOI: 10.1002/chem.201804529
|View full text |Cite
|
Sign up to set email alerts
|

Dual Gold‐Catalyzed Formal Tetradehydro‐Diels–Alder Reactions for the Synthesis of Carbazoles and Indolines

Abstract: This work reports ad ual gold-catalyzed tetradehydro-Diels-Alderr eaction for the synthesis of nitrogencontaining aromatic heterocycles. Under the catalytic system (IPrAuNTf 2 /DIPEA), indolinesa nd carbazoles as well as other N-containinga romatic heterocyclesw ere prepared in high yields with good functional group tolerance. Unlike the traditional thermalt etradehydro-Diels-Alder reactions, diluted reaction concentration and radical prohibitors are not required for this protocol. Experimental data support am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Gem ‐diaurated species 10 and σ,π‐digold complex 11 were also suggested to participate in the mechanism, where a dual catalyst transfer from 8 to substrate 3 is invoked. The very same transformation in the presence of (IPr)AuNTf 2 (10 mol%) and DIPEA (10 mol%) in 1,2‐dichloroethane at 80 °C was reported by Zi and co‐workers shortly after our publication [5] . The authors suggested that in the case of aryl‐substituted ynamides, a 6π electrocyclization would produce 7 from 6 .…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Gem ‐diaurated species 10 and σ,π‐digold complex 11 were also suggested to participate in the mechanism, where a dual catalyst transfer from 8 to substrate 3 is invoked. The very same transformation in the presence of (IPr)AuNTf 2 (10 mol%) and DIPEA (10 mol%) in 1,2‐dichloroethane at 80 °C was reported by Zi and co‐workers shortly after our publication [5] . The authors suggested that in the case of aryl‐substituted ynamides, a 6π electrocyclization would produce 7 from 6 .…”
Section: Introductionsupporting
confidence: 74%
“…The very same transformation in the presence of (IPr)AuNTf 2 (10 mol%) and DIPEA (10 mol%) in 1,2-dichloroethane at 80°C was reported by Zi and co-workers shortly after our publication. [5] The authors suggested that in the case of aryl-substituted ynamides, a 6π electrocyclization would produce 7 from 6. We report herein our complete experimental and computational investigations on the mechanism of this transformation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several recent reports have harnessed dual gold-catalysts in cycloaromatisations via TDDA reactions of enediynes. [3][4][5][6][7] In these cases the enediyne is not fully conjugated but has the alkyne and enyne units linked via a heteroatom tether leading to a diverse range of fused heterocyclic benzenoid structures of biological signicance (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the usual standard tetradehydro-Diels-Alder reaction, Wang's adaptation proceeds without the requirements of a dilute reaction mixtures and the use of radical-trapping agents, thus making it a practical protocol. 58 Scheme 37 General approach towards the synthesis of indolines and carbazoles 146 via a dual Gold-catalyzed tetradehydro-Diels-Alder reaction, with a highlight of the crucial mechanistic steps.…”
Section: Synthesis Of Indolines and Carbazoles Via A Dual Gold-catalyzed Tetradehydro-diels-alder Reactionmentioning
confidence: 99%